Natural Medicines Used in the Traditional Tibetan Medical System for the Treatment of Liver Diseases - Li, Qi; Li, Hai-Jiao; Xu, Tong; Du, Huan; Huan Gang, Chen-Lei; Fan, Gang; Zhang, Yi (Frontiers in Pharmacology, 2018)
Liver disease is one of the most risk factors threatening human health. It is of great significance to find drugs that can treat liver diseases, especially for acute and chronic hepatitis, non-alcoholic fatty liver disease and liver cancer. The search for drugs with good efficacy from traditional natural medicines has attracted more and more attention. Tibetan medicine, one of the China's traditional medical systems, has been widely used by the Tibetan people for the prevention and treatment of liver diseases for hundreds of years. The present paper summarized the natural Tibetan medicines that have been used in Tibetan traditional system of medicine to treat liver diseases by bibliographic investigation of 22 Tibetan medicine monographs and drug standards. 193 species including 181 plants, 7 animals and 5 minerals were found to treat liver diseases in traditional Tibetan medicine system. The most frequently used species are Carthamus tinctorius, Brag-zhun, Swertia chirayita, Swertia mussotii, Halenia elliptica, Herpetospermum pedunculosum, and Phyllanthus emblica. Their names, families, medicinal parts, traditional uses, phytochemicals information, and pharmacological activities were described in detail. These natural medicines might be a valuable gift from the old Tibetan medicine to the world, and would be potential drug candidates for the treatment of liver diseases. Further studies are needed to prove their medicinal values in liver diseases treatment, identify bioactive compounds, elucidate the underlying mechanism of action, and clarify their side effects or toxicity with the help of modern phytochemical, pharmacological, metabonomics, and/or clinical trial methods.